Lateral Condyle Impaction Fracture Reduction With Anterior Cruciate Ligament Reconstruction, Medial Collateral Ligament Reconstruction, and Repair of Lateral Meniscus Radial Tear After a High-Grade Pivot-Shift Injury - Luke V. Tollefson, B.S.; Evan P. Shoemaker, B.A.; Nathan J. Jacobson, M.D.; Erik L. Slette, M.D.; Robert F. LaPrade, M.D., Ph.D. (Arthroscopy Techniques)
The pivot shift is a common injury mechanism during an anterior cruciate ligament injury in which the tibia rotates anterolaterally with a combined valgus force. This mechanism can lead to bone bruising and even impaction fractures of the lateral femoral condyle. High-grade pivot-shift cases can also lead to pinching of the lateral meniscus, causing tearing. In cases with a sufficient valgus force, combined injuries, including the medial collateral ligament, can also occur. This video technique describes the reconstruction of the anterior cruciate ligament and medial collateral ligament, lateral meniscus radial tear repair, and reduction of a lateral femoral condyle impaction fracture caused by a high-grade pivot-shift injury.